Intraoperative cryo nerve block during lower extremity amputation prevents the development of phantom limb pain - Lizabeth A. O’Connor, DMSc, MPH, PA-C; Curtis C. Quinn, MD, FACS; Bryan Houseman, DO (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Phantom limb pain is the experience of painful sensations in an amputated limb. It is highly prevalent with unclear etiology. There is no consensus regarding the ideal prevention and treatment of this condition. We report a case of a 58-year-old female who underwent a right below-knee amputation with concomitant application of cryo nerve block to the tibial, deep, and superficial peroneal nerves. The patient denied phantom limb pain at 1 year following surgery. This case highlights the potential benefits of cryo nerve block for postoperative pain reduction and prevention of phantom limb pain.